Modelagem da relação entre a mortalidade por câncer e indicadores de condições de vida da população idosa do Nordeste do Brasil - Carvalho, João Batista (2018)
With a population aging process already in progress in 2010, the Brazilian Northeast presented expressive proportional values of deaths due to chronic-degenerative diseases, emerging neoplasias, mainly prostate, female breast and lung cancer in both sexes, in a context of social and economic inequalities. The objective was to evaluate the relationship between mortality rates by the main types of cancer and indicators of the living conditions of the elderly population of the Brazilian Northeast by sex. A cross-sectional ecological study to the years 2010 and 2015 was adopted to the 188 micro regions of the Northeast, using structural equation modeling. Population data, deaths and indicators of living conditions were extracted from IBGE, SIM/MS, and SISAP-Idoso, respectively. Due to problems in the quality of information on basic death causes, the death data were corrected for underreporting, ill-defined causes and garbage codes. The recovery of a considerable number of deaths made it possible to obtain a greater accuracy in the estimation of mortality rates at micro region and state levels. An increase in mortality rates was observed in the period. Structural equations modeling presented a robust model with significance for some indicators of living conditions. Rates were higher in microregions with lower percentages of illiterate elderly and in poverty, lower dependency ratio and higher percentage of elderly people living in households with running water. It was concluded that the results showed a trend of increased deaths of the elderly by the main types of cancer in the region, with higher levels in the microregions with better indicators of living conditions.